Covishield Vaccine Coverage and its adverse effects among the Staffs of Nepalgunj Medical College Banke - Yadav, Binod Kumar; Choudhary, Ram Chandra; Shah, Gaurav Jung; Siddiqui, Saharoj (Journal of Nepalgunj Medical College, 2022)
Introduction: The corona virus disease-19 pandemic is an ongoing global health crisis and the greatest challenge we have been facing right now in the most peculiar ways. It has caused huge loss of lives and has severely affected the global economy and financial markets. Vaccines are a new critical tool to fight this voracious battle. They have been released in several parts of the world. Although the safety and efficacy of these vaccines have been discussed, we know very little about the post-vaccination experience outside clinical trial situations. Adequate information about the effects of the vaccine can aware the public remove misconceptions and increase vaccine acceptability. Aims: To know the percentage of Covishield vaccine coverage and its adverse effects among the staffs of Nepalgunj Medical College.Methods: A descriptive cross-sectional study was conducted among the vaccinated 91 out of 116 staff members of Nepalgunj Medical College (NGMC), Baijanath Rural Municipality-1, Banke.Results: Out of 91 persons, 15.4%(14) developed headache, 20%(18) developed fever, and 8.7%(17) developed body aches. Of those who developed post-vaccination side effects 47%(16) of the persons were from age group 36-55years,17%(1) of them between age group 55-65 years, and none above 65 years developed fever. 20%(13) of total male and 35%(5) of total female developed fever within 96 hours after receiving first dose of Covishield AstraZeneca vaccine.Conclusion: Most of the study subjects reported milder side effects which lasted for less than 5 days. No casualties were reported. Local pain and swelling at the injection site, headache and fever were the most common side effects. The side effects were more common in younger individuals and women.